Rancang bangun sistem pengelolaan konten marketing dan e-commerce berbasis lintas platform - Achmad Rizki Susanto; Fauziyah Fauziyah; Sharyanto Sharyanto (Jurnal Manajamen Informatika Jayakarta, 2022)
PT Pangansari Utama is a company engaged in the food industry, it has several main obstacles, namely still using third-party e-commerce applications, namely Tokopedia and storing customer data in the Tokopedia database which often causes problems such as human error, namely the delivery party often forgets to update the status of transactions that make sales reports late and not on schedule. Solving the problem from PT Pangansari Utama, we need an e-commerce information system that can of course store customer data in a safe and structured manner as well as a system that can help admin, finance, and delivery to manage transactions more easily. The customer purchase transaction manager will be directed to finance Pangsari so that there is no more delay in transferring funds, an information system is needed that can change the transaction status automatically if the product has been received by the customer, an information system is needed that can report all sales data into day, week reports , month and year automatically.